Establishment of nitrous oxide (N2O) dynamics model based on ASM3 model during biological nitrogen removal via nitrification - Lv, Ying (Environmental technology, 2022)
Nitrous oxide (N2O), as one of the six greenhouse gases, is mainly produced in the biological nitrogen removal process of wastewater treatment plants (WWTPs). Establishing the N2O kinetic model can provide insight into the N2O generation mechanism and regulate its production. This work uses Activated Sludge Model NO.3 (ASM3) as the basic framework, combines organic storage with endogenous respiration theory, and couples ammonia-oxidizing bacteria (AOB) denitrification pathway and the NH2OH/NOH model to establish a kinetic model. Meanwhile, the Sequencing Batch Reactor (SBR) process with artificial simulated urban domestic sewage was used as the carrier; MATLAB and EXCEL software were used as tools to establish a model calculation programme. The simulated values obtained by substituting the operating conditions of the SBR process into the model and the measured values of the SBR process were analysed. The correlation coefficient (R2) between the experimental values and simulated values obtained for the 5 components of COD, ammonia, nitrite, nitrate and total N2O is 0.952, 0.996, 0.902, 0.991 and 0.956, respectively, which indicates that the N2O kinetic model has great consistency, this further shows that the established model modelling mechanism is clear and accurate, and provides a new method for the N2O dynamic model